Transfer of training among graduates of technical vocational education and training (TVET) institution in Malaysia / Sarah Mardhiah Selamat, Sarina Muhamad Noor and Noraini Nasirun - Selamat, Sarah Mardhiah; Muhamad Noor, Sarina; Nasirun, Noraini (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Transfer of training is one of the areas that become a main concern for most Human Resource managers. As it involves high costs, organizations attempt to make utmost benefits of any training programs participated by their employees. Similarly with the educational institutions, especially those that offer technical education whose aim is to enhance skills among participants. Moreover, the main objective of the educational institutions is to equip students with a better knowledge so that they will make a wise decision and participate in economic development. Based on such premises, this study was conducted to determine the relationship among transfer design, self-efficacy, performance feedback and transfer of training. Besides, this study also intended to determine the employability rate among graduates of Technical Vocational Education and Training (TVET) institution. A set of questionnaires was administered to graduates who attended convocation at their institution in 2013. With a respond rate of 51%, the findings indicate that there was a significant relationship between the studied variables. However, only two of these variables explained transfer of training of these graduates. The paper also discussed the implications of this research towards the institutions especially in the higher learning institutions that focused on vocational training and entrepreneurship education. This study contributes to the understanding of transfer of training of technical institutions graduates.